Proses Peningkatan Hasil Pembelajaran IPA melalui Media Pembelajaran dan Metode Eksperimen di SD IT Miftahul Jannah Bandar Selamat, Kec. Medan Tembung - Aufa Aufa; Aulia Luthfi Fathoni; Nadia Ulandari; Muhammad Oki Dermawan; Zaira Asmi Lubis (Departement of Mathematics Education, 2023)
This research is motivated by the existence of problems that arise in students caused by the learning process still using the lecture method, causing the learning process to seem monotonous and cause a feeling of boredom and boredom in students and there is no meaningful learning experience, so that student learning outcomes are less good. The goal to be achieved in this research is to find out the learning process by using experimental methods and learning media as well as improving student learning outcomes after using experimental methods and learning media. Currently learning science in elementary schools, the teacher's role in the learning process is still dominant. In learning, the teacher delivers teaching material in front of the class using the lecture method only while the students just sit, listen and take notes on what is material in the science lesson. Such learning conditions result in students being less active and not directly involved in finding the meaning of learning to be achieved. The purpose of the research conducted was to improve the learning outcomes of class VI students at SD IT Miftahul Jannah, Bandar Selamat Village, Kec. Medan Tembung in science subjects on electrical energy through experimental methods and teaching aids. This study uses a qualitative method with a descriptive approach. This data collection technique takes place with the interview process.How to use learning media with this experimental method is quite effective in helping students find methods to increase their understanding of the subject matter that has been delivered.